Successful treatment with 4‐phenylbutyrate in a patient with benign recurrent intrahepatic cholestasis type 2 refractory to biliary drainage and bilirubin absorption. Issue 2 (15th September 2015) - Hayashi, Hisamitsu; Naoi, Sotaro; Hirose, Yu; Matsuzaka, Yusuke; Tanikawa, Ken; Igarashi, Koji; Nagasaka, Hironori; Kage, Masayoshi; Inui, Ayano; Kusuhara, Hiroyuki
Abstract : Aim: Benign recurrent intrahepatic cholestasis type 2 (BRIC2) is caused by mutations in ABCB11, a gene encoding the bile salt export pump (BSEP) that mediates biliary bile salt secretion, and presents with repeated intermittent cholestasis with refractory itching. Currently, no effective medical therapy has been established. We previously provided experimental and clinical evidence suggesting the therapeutic potential of 4‐phenylbutyrate (4PB) for the cholestatic attacks of BRIC2. Methods: After examining the potential therapeutic use of 4PB treatment by in vitro studies, a patient with BRIC2 was treated p.o. with 4PB at gradually increasing doses (200, 350, and 500 mg/kg per day) for 4 months. Biochemical, histological and clinical data were collected. Results: The patient was diagnosed with BRIC2 because he had non‐synonymous mutations (c.1211A>G [p.D404G] and 1331T>C [p.V444A]) in ABCB11, reduced hepatocanalicular expression of BSEP and low biliary bile salt concentrations. In vitro analysis showed that 4PB treatment partially restored the decreased expression of BSEP caused by p.D404G mutation. During the first 2 months of 4PB therapy at 200 and 350 mg/kg per day, the patient had no relief from his symptoms. No beneficial effect was observed after additional treatment with bilirubin absorption and endoscopic nasobiliary drainage. However, after starting treatment at a dose of 500 mg/kg per day, the patient's liver function tests and intractable itching were markedly improved. No apparent side‐effects were observed during or after 4PB therapy. The symptoms relapsed within 1.5 months after cessation of 4PB therapy. Conclusion: 4PB therapy would have a therapeutic effect on the cholestatic attacks of BRIC2.